The Influence Of Leadership Style, Work Culture And Motivation On Nurse Performance At Bantuan Hospital 01.08.01 - Margaretha Pasaribu; Zulfendri (TOUR HEALTH JOURNAL, 2022)
Background: Employee performance is influenced by several factors including leadership style, work culture and motivation that will affect the quality of service provided to the community. The purpose of this study was to determine the effect of leadership style, work culture and motivation on nurse performance at the Bantuan Hospital 01.08.01. Purpose: This study aims to describe the influence of leadership style, work culture and motivation on nurse performance at Bantuan Hospital 01.08.01. Method: This type of research is an explanatory research, the study was conducted in March-August 2018, the population and sample in this study were all nurses at the Hospital Assistance 01.08.01. Kisaran, North Sumatra Province as many as 37 people. Results: Situational leadership style, work culture and motivation partially have a positive and significant effect on the performance of nurses at Bantuan Hospital 01.08.01. Discussion and Conclusion: Simultaneously, the leadership style is the most dominant factor that greatly influences the performance of nurses in the Sub-Hospital 01.08.01. Where a good leadership style has a 24,404 times greater chance of a nurse's performance compared to a bad leadership style. this study are expected to make Hospital Leaders ranging from the director's supervisor to the head of the room need to apply leadership style that leads to a partisative style so that nurses are more responsible in carrying out services to patients and provide salary and salary bonuses in accordance with the nurse's performance and also give awards for good performance achievements such as promotion or other matters as well as making training - training so that nurses are able to increase knowledge in order to achieve effective and efficient performance.